Co-feeding of inert diet from mouth opening does not impair protein utilization by Senegalese sole (Solea senegalensis) larvae - Engrola, S. (2014)
In most marine species inert diets alone have a poor ability to sustain fish larvae growth and development. Furthermore, results of co-feeding inert diets and live prey are variable, which may be related to the effect of inert diets on digestive maturation and subsequently protein utilization. The aim of the present work was to investigate how different feeding regimes, live feed alone or co-fed with an inert diet, influence protein utilization in Senegalese sole larvae. Feed intake, protein absorption, protein retention and protein catabolism were estimated in sole from 8 to 35 days after hatching (DAH), using 14C-labelled Artemia protein and posterior incubation in metabolic chambers. Postlarvae that were co-fed with an inert diet from mouth opening ate more than postlarvae fed Artemia alone at most sampling ages. Sole Artemia protein digestibility ranged from 56.97 (16 DAH) to 81.32% (22 DAH). Sole larvae that were fed a second meal had a slightly, though significant, higher digestibility than sole fed a single meal. Digestibility was lower in co-fed sole during metamorphosis climax, and similar between treatments at other developmental stages. Retention efficiency remained almost constant during early development, and was not affected by feeding regime. In short, co-feeding of an inert diet from mouth opening does not impair protein utilization by Senegalese sole larvae.